2020
DOI: 10.1186/s12876-020-01461-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic predominant presentation of Kawasaki disease in adolescence case report and review of literature

Abstract: Background Kawasaki Disease (KD) is the most common paediatric vasculitis affecting small to medium arteries. Although the average age of diagnosis is 3.4 years with a well-defined clinical presentation, older patients with KD including adolescent and adult patients demonstrate a less classical presentation with prominent findings including hepatitis, cervical lymphadenopathy, and arthralgia. We describe a case of an adolescent presentation of Kawasaki Disease presenting with a predominantly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Vergine et al ( 38 ) and Momenah et al reported that older children above the age of 9 years accounted for 7.5% of their KD patients, and that they had a higher risk of coronary artery abnormalities ( 39 ), especially those who presented with febrile cholestasis. In addition, Pratap et al found that hepatic-predominant manifestations were more common in older children who were more refractory to treatment ( 40 ). Therefore, some experts have concluded that a high level of suspicion should be maintained in children who present with febrile jaundice and atypical KD, especially among older children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Vergine et al ( 38 ) and Momenah et al reported that older children above the age of 9 years accounted for 7.5% of their KD patients, and that they had a higher risk of coronary artery abnormalities ( 39 ), especially those who presented with febrile cholestasis. In addition, Pratap et al found that hepatic-predominant manifestations were more common in older children who were more refractory to treatment ( 40 ). Therefore, some experts have concluded that a high level of suspicion should be maintained in children who present with febrile jaundice and atypical KD, especially among older children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various studies and case reports in the past describing the varied manifestations of IKD. Pratap et al 10 described KD in an adult with predominant hepatic involvement which is rare. Hu C et al 11 reported KD in a 4 years old boy with predominant gastrointestinal symptoms with signs of gastrointestinal haemorrhage on Endoscopy.…”
Section: Discussionmentioning
confidence: 99%